Locating Imagination in Popular Culture Place, Tourism and Belonging - van Es, Nicky; Reijnders, Stijn; Bolderman, Leonieke; Waysdorf, Abby (Routledge Research in Cultural and Media Studies, 2021)
Locating Imagination in Popular Culture offers a multi-disciplinary account of the ways in which popular culture, tourism and notions of place intertwine in an environment characterized by ongoing processes of globalization, digitization and an increasingly ubiquitous nature of multi-media. Centred around the concept of imagination, the authors demonstrate how popular culture and media are becoming increasingly important in the ways in which places and localities are imagined, and how they also subsequently stimulate a desire to visit the actual places in which people's favourite stories are set. With examples drawn from around the globe, the book offers a unique study of the role of narratives conveyed through media in stimulating and reflecting desire in tourism. This book will have appeal in a wide variety of academic disciplines, ranging from media and cultural studies to fan- and tourism studies, cultural geography, literary studies and cultural sociology.